Line balancing production in a shoe’s company by metaheuristic tabu search - Coletti Romero, Erwin (2018)
The Assembly Line Balancing problem (ALBP) consists of assigning tasks to an ordered sequence of stations in order to satisfy the precedence relations between the tasks and optimize some performance measure. When a production line is not well balanced, there are bottlenecks, discontent among the workers because, there will always be some who work more than others in the same units of time, delays in delivery etc. It is a NP-hard problem that needs to be solved in both large and small companies. This article presents a BLP in a medium shoe factory in the city of Lima-Peru. Times and costs of the production process of the 2011 winter season were collected. The metaheuristic taboo search was applied, finding a model for the distribution of workers to the production activities, which was implemented in the winter season of 2012, achieving an improvement in efficiency of 75%. Likewise, the reprocesses for failures had a reduction of 8.21%, thus obtaining savings for the company under study. To implement the taboo search, a computer program was carried out.